Experiments in indigenous church music among the Batetela - Shaffer, Jacquiline (International Library of African Music, 1956)
The Batetela tribe of the Kasai of the Belgian Congo was reached by Protestant missionaries forty years ago. They entered the territory around Wembo Nyama, and, establishing it as their point of departure, they set out in all directions ministering to the vast area of Otetela speaking people. It is probably safe to assume that mission work began here in the same manner as in other parts of the Congo; the early missionaries found little or nothing in the old ways of the people upon which they could build the type of Christian faith which had been revealed to them. This was certainly true in the area of music. From the very earliest beginnings, as far as the author can discover, a strict ban was placed on all forms of native music, musical instruments, and rhythmical devices which were feared would encourage the people in their old practices. Thus began the “westernization” of music among the Batetela Christians.
Keywords: African Music; Belgian Congo